Interaction Between Hyperhomocysteinemia, Mutated Methylenetetrahydrofolatereductase (MTHFR) and Inherited Thrombophilic Factors in Recurrent Venous Thrombosis - Keijzer, Miranda B. A. J.; den Heijer, Martin; Blom, Henk J.; Bos, Gerard M. J.; Willems, Huub P. J.; Gerrits, Wim B. J.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 2002)
Venous thrombosis is a multicausal disease involving acquired and genetic factors. In this study we investigated a possible interaction between hyperhomocysteinemia (fasting or postload) and factor V Leiden or prothrombin G20210A on the risk of recurrent venous thrombosis. We also looked at the risk due to mutations in the MTHFR-gene (C677T and A1298C).We performed a case-control study in 171 patients with a history of recurrent venous thrombosis and 461 control subjects from the general population. Hyperhomocysteinemia (fasting or 6 h after an oral methionine load) was defined as a homocysteine concentration above the 90th percentile of the distributions in the control group.The odds ratio (adjusted for age and sex) for recurrent venous thrombosis was 1.8 (95%CI: 1.1 to 3.0) for fasting hyperhomocysteinemia, 5.1 (95%CI: 3.0 to 8.6) for factor V Leiden and 1.8 (95%CI: 0.7 to 4.2) for prothrombin G20210A. We found 14 patients and 3 controls with both hyperhomocysteinemia and factor V Leiden, which yielded an odds ratio of 11.6 (95%CI: 3.2 to 42.5). We found no interaction between hyperhomocysteinemia and prothrombin G20210A. The relative risk for MTHFR 677CT was 1.6 (95%CI: 1.1 to 2.4) and for MTHFR 677TT was 1.4 (95%CI: 0.7 to 2.8). The combined risk for MTHFR 677TT and factor V Leiden was 18.7 (95%CI: 3.3 to 108).We conclude that hyperhomocysteinemia and factor V Leiden are risk factors for recurrent venous thrombosis. The risk of thrombosis appeared high for individuals who had both risk factors.
Keywords: Homocysteine; venous thrombosis; factor V Leiden; prothrombin G20210A; MTHFR